Informal risk management practices for cost overruns in Malaysian public linear projects / Marina Musa - Musa, Marina (Institute of Graduate Studies, UiTM, 2015)
The Malaysian construction industry is associated with a high degree of risk due to the nature of its business activities, process, environment and organisation. However, systematic risk management is not practiced in most public construction projects in Malaysia. This situation leads to project failure such as cost overrun, schedule slip and poor quality performance. Risk management is important to improve project performance in term of cost, time and quality. There is little information on the way informal reactive risk management practice contributes either positively or negatively to the project outcomes. The aim of this study was to understand the influence of informal risk management practice to mitigate cost overruns in Malaysian linear-type public projects. It involved projects that had cost overruns and were supervised by Malaysian government technical agencies on behalf of Malaysian ministries and other government agencies. A qualitative-quantitative research methodology was used. The qualitative study involved interviews with a triad of client, consultant and contractor participants in 15 projects. Inductive content analysis produced 16 categories of risk factors, 3 categories of risk treatments, 6 categories of barriers to risk treatment usage and 5 categories of coping actions to overcome the barriers to risk treatment usage…